The role of plasminogen activator inhibitor type 1 in the inflammatory response to local tissue injury - RENCKENS, R.; ROELOFS, J. J. T. H.; DE WAARD, V.; FLORQUIN, S.; LIJNEN, H. R.; CARMELIET, P.; VAN DER POLL, T. (Journal of thrombosis and haemostasis, 2005)
Background: The plasma levels of the plasminogen activator‐inhibitor type 1 (PAI‐1) are consistently elevated in patients with sterile tissue injury, often accompanied by a systemic acute phase protein response. It remains unknown, however, whether and to what extent PAI‐1 affects the host response to trauma. Methods and results: By using the well‐established murine model of turpentine‐induced tissue injury we compared local and systemic inflammatory responses in PAI‐1 gene‐deficient (PAI‐1–/–) and normal wild‐type (Wt) mice. Subcutaneous turpentine injection elicited strong increases in PAI‐1 protein concentration in plasma and at the site of injury, but not in liver. PAI‐1 mRNA was locally increased and expressed mainly by macrophages and endothelial cells. PAI‐1 deficiency greatly enhanced the early influx of neutrophils to the site of inflammation, which was associated with increased edema and necrosis at 8 h after injection. Furthermore, PAI‐1–/– mice showed a reduced early interleukin (IL)‐6 induction with subsequently lower acute phase protein levels and a much slower recovery of body weight loss. Conclusion: These findings suggest that PAI‐1 is not merely a marker of tissue injury but plays a functional role in the local and systemic host response to trauma.